The evaluation of electromagnetic shielding properties of CFRP/metal mesh hybrid woven laminated composites. (November 2018) - Tugirumubano, Alexandre; Vijay, SJ; Go, Sun Ho; Shin, Hee Jae; Ku, Kwac Lee; Kim, Hong Gun
Carbon fiber-reinforced plastic (CFRP) composites, owing to their lightweight and strength-weight ratio, are being used in many applications to replace traditional metallic materials and their alloys. The combination of polymeric composites with metallic materials can provide a significant impact in engineering applications. This paper evaluates electromagnetic interference shielding of bimetal-carbon prepreg fibers textile composite materials. Prepreg carbon fibers and metal wire mesh are used to make electromagnetic interference shielding samples. The material samples consist of making plain weaves of metal wire mesh and carbon prepreg and stack them with prepreg carbon fiber layers. In order to produce plain woven fabrics, wefts were made of prepreg carbon fibers and warps were made of wire meshes. In each woven fabric, two yarns of different metal wire meshes were alternated one after another. The combination of conductive wire meshes such as stainless steel-copper, stainless steel-nickel, and copper-nickel in a woven fabric was considered. The electromagnetic shielding effectiveness was evaluated for each textile composite material based on ASTM 4935-99. Results showed a possible application of these materials for electromagnetic interference shielding with higher absorption. The best electromagnetic interference shielding performance was obtained for a combination of stainless steel-copper-CFRP with a shielding effectiveness of 131.6 dB. The absorption losses for all samples were about 82% of electromagnetic interference shielding effectiveness. The mechanical properties and scanning electron image of fabricated samples were also investigated.